2009
DOI: 10.1002/jhm.549
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in as‐needed sedative use by limiting nighttime sleep disruptions from hospital staff

Abstract: Small modifications in hospital routines, especially in the timing of vital signs and routine medication administration, can significantly reduce sedative use in unselected hospital patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…Our results for reported sleep duration and VSH scores are consistent with previous reports in general medicine patients [7,13, 14]. We also performed a comprehensive survey of factors that may be associated with nighttime sleep quality, using three different quality measurements (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Our results for reported sleep duration and VSH scores are consistent with previous reports in general medicine patients [7,13, 14]. We also performed a comprehensive survey of factors that may be associated with nighttime sleep quality, using three different quality measurements (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies indicated that initiating quiet times was successful in decreasing noise levels 20,23 and in improving patients' sleep quality. 2,33 Further, as mentioned earlier, low mean SPLs should not be interpreted as an indication that disturbing sounds are not present. In future, an analysis to determine the sources of the peak SPLs should be conducted, as should interviews with patients to determine which sounds they find most disturbing, so that measures can be taken to decrease the sources of those specific sounds.…”
Section: Discussionmentioning
confidence: 91%
“…8 A lack of sleep has also been associated with, but is not necessarily the cause of, ICU delirium. 32 Recently, Bartick et al 33 reported that decreasing sleep disruptions by lowering lighting levels, having nurses avoid waking patients for measurement of vital signs, and instigating a "quiet time" resulted in decreased use of sedatives among patients.…”
mentioning
confidence: 99%
“…(38) Furthermore, interventions that reduce the stress of hospitalization by optimizing sleep and keeping patients mentally and physically active during their stay may have a beneficial effect on medication adherence after discharge. (39)…”
Section: Discussionmentioning
confidence: 99%